Techniques of the world's best: Reception with Reinder - Held, W.; Gerbrands, T. (The Coach, 1998)
Reinder Nummerdor was during the European Championship of 1997 the only new player in the first six of Olympic Champion Holland. A lot of people thought that he was not able to handle the pressure, but after the final against Yugoslavia the young Dutchman (21) was chosen to be the best reception-player of the championship. We try to analyse this performance. This series of pick-up pictures starts with articles in which players from the best teams in the world demonstrate their most successful techniques. The players themselves and their club- or national coaches give their considered opinions on the pictures and tips on the key sequences in the technique, with helpful training tips to back them up.